Elevated oxysterol and N‐palmitoyl‐O‐phosphocholineserine levels in congenital disorders of glycosylation. Issue 2 (3rd February 2023) - Dang Do, An N.; Chang, Irene J.; Jiang, Xutian; Wolfe, Lynne A.; Ng, Bobby G.; Lam, Christina; Schnur, Rhonda E.; Allis, Katrina; Hansikova, Hana; Ondruskova, Nina; O'Connor, Shawn D.; Sanchez‐Valle, Amarilis; et al.
Abstract: Congenital disorders of glycosylation (CDG) and Niemann‐Pick type C (NPC) disease are inborn errors of metabolism that can both present with infantile‐onset severe liver disease and other multisystemic manifestations. Plasma bile acid and N‐ palmitoyl‐ O‐ phosphocholineserine (PPCS) are screening biomarkers with proposed improved sensitivity and specificity for NPC. We report an infant with ATP6AP1‐CDG who presented with cholestatic liver failure and elevated plasma oxysterols and bile acid, mimicking NPC clinically and biochemically. On further investigation, PPCS, but not the bile acid derivative N ‐(3β, 5α, 6β‐trihydroxy‐cholan‐24‐oyl) glycine (TCG), were elevated in plasma samples from individuals with ATP6AP1‐, ALG1‐, ALG8‐, and PMM2‐CDG. These findings highlight the importance of keeping CDG within the diagnostic differential when evaluating children with early onset severe liver disease and elevated bile acid or PPCS to prevent delayed diagnosis and treatment.